Association between Maternal Vitamin B-12 Deficiency and Early Neurodevelopmental Biomarkers in Breastfed Neonates: Vitamin B-12 Deficiency and Neurodevelopmental Biomarkers in Breastfed Neonates - Iqbal, Javeria; Hussain, Ansar; Shah, Maarij Ullah; Iqbal, Shahid; Jan, Muhammad Arif; Rasheed, Farah (Pakistan Journal of Health Sciences, 2025)
Vitamin B-12 plays a vital role in fetal brain development and early neurological function. Exclusively breastfed neonates are highly dependent on maternal B-12 stores and are at increased risk for early neurodevelopmental deficits in cases of maternal deficiency. However, evidence on this association during the neonatal period remains limited, especially in low-resource settings. Objectives: To assess the association between maternal vitamin B-12 deficiency and early neurodevelopmental outcomes in exclusively breastfed neonates within the first month of life. Methods: This cross-sectional analytical study was conducted on 91 mother-infant pairs. Maternal serum B-12 levels were measured postpartum, and infants were evaluated within the first 28 days using standardized neurodevelopmental assessments, including cognitive, motor, and language scores, as well as clinical markers like visual tracking, muscle tone, and developmental reflexes. Data were analyzed using SPSS, version 26.0 and associations were tested through independent t-tests and Chi-square analyses (p<0.05 considered significant). Results: Vitamin B-12 deficiency was found in 35.2% of mothers. Among the exclusively breastfed subgroup (n=46), no statistically significant differences were observed in cognitive (p=0.480), motor (p=0.473), or language scores (p=0.544) between neonates of B-12-deficient and B-12-sufficient mothers. Similarly, visual tracking deficits, abnormal muscle tone, and neurodevelopmental delay showed no significant associations with maternal B-12 status. Conclusions: Maternal vitamin B-12 deficiency did not demonstrate a measurable impact on early neurodevelopmental biomarkers in exclusively breastfed neonates during the first month of life. Larger longitudinal studies are needed to determine long-term consequences and guide maternal nutrition policies.